How Did We Learn During the Pandemic? The Perception of University Students in Chile - Urcia, Elsa piedad cabrera-m; Ordero, Claudia constanza pizarro-c; Gonzalez Sanzana, Alvaro; Oval Soto, Carmen Paz; Enriquez, VERoNICA VILLARROEL-H (My University, 2024)
The coronavirus (COVID-19) pandemic unleashed a series of changes in the way of teaching and learning at all educational levels. While remote teaching was the strategy used to guarantee the continuity of learning all over the world, we still lack of body of knowledge that would allow us to understand its implementation from the standpoint of the learner. With that in mind, this study sought to find out the variables that influence the perception of learning during the pandemic on the part of Chilean university students, as well as to characterize the barriers and facilitators of the learning process in remote education. A mixed methodology was applied, based on the analysis of an online survey of 1677 students in 34 Chilean universities (which included public and private ones as well as universities in both the capital and the provinces). The results show that the didactics and participation are variable predictors of the perception of learning on the part of the student body, and there are findings which suggest that key aspects in the design and implementation of processes of remote teaching should be taken into account.
Keywords: teaching; higher education; learning; pandemics; chile